Implementation of Saurp for Mobile Network (International Journal of Engineering and Computer Science, 2018)
Delay Tolerant Networks (DTNs) that are possibly composed of a vast number of devices such as smart phones of diverse capacities in terms of energy resources and buffer spaces. We introduces protocol which is a novel multi-copy routing protocol called Self Adaptive Utility-based Routing Protocol (SAURP) for DTNs. SAURP has the ability to identify potential opportunities of forwarding messages to their destinations via a novel utility function based mechanism, where a suite of environment parameters, such as wireless channel condition, nodal buffer occupancy, and encounter statistics, are jointly considered. Taking a considerably small number of transmissions, it can reroute messages around nodes experiencing high buffer occupancy, wireless interference, and congestion. Thus SAURP utility function is proved to achieve optimal performance and it is also further analyzed via a stochastic modeling approach. To verify the developed analytical model, extensive simulations are conducted and are compared the proposed SAURP and shown that SAURP can perform all the counterpart multi-copy encounter-based routing protocols. These simulations are associated with the number of recently reported encounter-based routing approaches in terms of delivery ratio, delivery delay, and the number of transmissions required for each message delivery